Corrigendum of solubility of sodium 2-naphthalenesulfonate in binary (sodium chloride + water), (sodium sulfate + water) and (ethanol + water) solvent mixtures. (May 2019) - Li, Rongrong; Wang, Xiaoqiang; Cao, Lijuan; Zhan, Shiyun; Zhao, Jia; Jin, Yanxian; Chen, Yongfei; Han, Deman
Highlights: Some mathematical errors are identified about the published apparent thermodynamic analysis. The obtained solubility data were analyzed by Sun model. The thermodynamic properties were further evaluated by the famous van't Hoff equation. Abstract: Some mathematical errors are identified about the published apparent thermodynamic analysis of our previous work [J. Chem. Thermodynamics. 83 (2015) 1–5] for the dissolution process of sodium 2-naphthalenesulfonate in binary (sodium chloride + water), (sodium sulfate + water) and (ethanol + water) solvent mixtures. The purpose is not only to correct the previous mistakes, but also to further analyze thermodynamic properties in dissolution process with the famous van't Hoff equation. The results shown that the dissolution process of sodium 2-naphthalenesulfonate in these mixed solvents was not only spontaneous and endothermic but also entropy-driven.